Un nouveau stade pour Nantes ? Une production de sens mise à l’épreuve dans une fabrique conflictuelle de la ville - Maude Cournoyer-Gendron; Catherine Trudelle; Laurent Devisme (L'Espace Politique)
In this article, we intend to shed light on social and territorial dynamics that take place into a conflicted urbanism - looking at the case of the construction of a new football stadium in Nantes (France). Urban planning project or urban infrastructure projects nowadays present themselves with an important number of opposition, mobilizations, which are time to time highly mediatized. This assessment of the situation leads us to reflect upon the issue of conflit in urban and territorial planning. We will look at the production of meanings in the project, in terms of contradictory referents and representations that nourishes the project as well as the conflict. Drawing from a thematic analysis of interviews with the actors of the conflict surrounding the new stadium in Nantes, we see that the arguments put forward by the developers and the metropolis are questioned and contested through the production of counter-expertise regarding many aspects of the project (namely legal, architectural, technical) and through the mobilization of an alternative vision of what can be a stadium and an urban project in phase with the neighbors and the supporters.